SPEECH ACTS ANALYSIS OF THE DIALOGUE SPOKEN BY ELLE EVANS IN KISSING BOOTH 3 MOVIE - Ni Putu Dea Maharani, Ni Putu Dea Maharani (Journal of Humanities, Social Science, Public Administration and Management (HUSOCPUMENT), 2024)
Examining the illocutionary acts present in a movie dialogue can offer a valuable understanding of the tactics of communication employed by the characters and the underlying significance of their expressions. This study analyses speech act, especially illocutionary acts. This study collect data from a film entitled Kissing Booth 3 and focused on types of illocutionary act from the main character's utterances named Elle Evans. To analyze the data for this study, a qualitative descriptive methodology was employed. The researcher of this study used Searle's (1979) theory to categorize various illocutionary acts. There were 92 pieces of data discovered that had various types of illocutionary act including assertives, directives, commissives, expressives, and declaratives.